The Use of Calcium and Magnesium Hydroxides in Acid Mine Drainage Treatment - Sulaiman, Azli; Othman, Anuar; Ibrahim, Ismail; Mohd Rozi, Mohd Syahrir (EDUCATUM Journal of Science, Mathematics and Technology, 2019)
Reagent grade of calcium and magnesium hydroxides were used in this study to treat acid mine drainage (AMD) sample. AMD sample was collected from a tin tailing pond that located in Pengkalan Hulu, Perak which as pH around 2.87 ± 0.01. pH values had increased after treated with calcium hydroxide (Ca(OH)2) and magnesium hydroxide (Mg(OH)2), respectively. The maximum pH values obtained was 11.35 ± 0.01 by using 1.0 g of Ca(OH)2 at interval time 5 min. For Mg(OH)2, the highest pH value can be obtained was 7.22 ± 0.01 by using 1.0 g at interval time 30 min. The concentration of heavy metals such as aluminum, copper, iron, manganese, nickel and zinc were reduced after reaction with both materials. For examples aluminum concentration was reduced from 110.33 mg/L to 2.80 mg/L and 0.01 mg/L by using 1.0 g of Ca(OH)2 and Mg(OH)2, respectively.